(untitled) (Journal of Oriental Studies, 2020)
The elaborate treatment of the issues as the role of ethnic information as well as other information, the contexts of the use of ethnos names – ethnonyms in mass media products, the linguistic presentation of ethnic positive / negative data, their influence on consciousness of information consumers and their functions in press media of any country is considered very topical. The frequent occurrence of ethnos in various negative contexts may lead to the formation of negative associations on the ethnos in the consumer consciousness. That is why mass media is one of the mechanisms of controlling and influencing the public consciousness in positive or negative propaganda of the nation’s image, the national identity, national unity processes. In this regard, the study of the headlines of press publications is being realized as they have an impact on the formation of an opinion of a reader about a definite ethnos, the emergence of an ethnic stereotype in the society in general. Key words: ethnonymic headline, media discourse, ethnic stereotype, image of ethnos, content analysis